Protected intermetallic PtMn nanoparticles via thermal decomposition and annealing approach for highly active and durable electrocatalysts - Jung, Jae Young; Kim, Dong-gun; Kim, Sujin; Park, Yong-Seong; Kim, Nam Dong; Park, Subin; Lee, Eungjun; Yoo, Sung Jong; Kim, Pil (Elsevier BV, 2026)
Reducing the substantial platinum usage and enhancing stability in polymer electrolyte membrane fuel cells (PEMFCs) require the development of next-generation platinum catalysts. Platinum-based intermetallic catalysts with ordered crystal phase are known to exhibit high activity and stability for oxygen reduction reaction (ORR), a key reaction that determines fuel cell performance. However, the formation of ordered intermetallic structures typically requires high-temperature annealing processes, which result in particle agglomeration and reduced active surface area. In this study, PtMn alloy nanoparticles (NPs) were supported on carbon supports through thermal decomposition of Pt(acac)2 and Mn(acac)3 precursors in organic solvents. A protective layer composed of residual organic species naturally forms on the pristine PtMn NPs during synthesis and suppresses NP agglomeration while promoting ordered structure formation during subsequent high-temperature treatment. Under H2/N2 mixed atmosphere, the PtMn/C-2H800 showed highly dispersed PtMn intermetallic NPs. The mass activity of PtMn/C-2H800 exhibited 0.50 A mgPt-1, demonstrating approximately 2.5-fold improvement compared to commercial Pt/C (0.20 A mgPt-1), while showing excellent catalytic stability with only 8.7 % loss of active surface area after 20,000 cycles. The superior performance and durability are attributed to the optimized adsorption energy of oxygen species due to the presence of protected PtMn intermetallic NPs that suppresses surface oxidation. Our findings demonstrate that combining precursor decomposition-based synthesis with protective layer formation represents an effective approach for improving both performance and durability of PtMn alloy catalysts.